Phylogenetic evidence of the intercontinental circulation of a Canine distemper virus lineage in the Americas (2019)
Canine distemper virus (CDV) is the cause of a multisystem disease in domestic dogs and wild animals, infecting more than 20 carnivore and non-carnivore families and even infecting human cell lines in in vitro conditions. Phylogenetic classification based on the hemagglutinin gene shows 17 lineages with a phylogeographic distribution pattern. In Medellín (Colombia), the lineage South America-3 is considered endemic. Phylogenetic studies conducted in Ecuador using fragment coding for the fusion protein signal peptide (Fsp) characterized a new strain belonging to a different lineage. For understanding the distribution of the South America-3 lineage in the north of the South American continent, we characterized CDV from three Colombian cities (Medellín, Bucaramanga, and Bogotá). Using phylogenetic analysis of the hemagglutinin gene and the Fsp region, we confirmed the circulation of CDV South America-3 in different areas of Colombia. We also described, for the first time to our knowledge, the circulation of a new lineage in Medellín that presents a group monophyletic with strains previously characterized in dogs in Ecuador and in wildlife and domestic dogs in the United States, for which we propose the name “South America/North America-4” due its intercontinental distribution. In conclusion, our results indicated that there are at least four different CDV lineages circulating in domestic dogs in South America: the Europe/South America-1 lineage circulating in Brazil, Uruguay, and Argentina; the South America-2 lineage restricted to Argentina; the South America-3 lineage, which has only been reported in Colombia; and lastly an intercontinental lineage present in Colombia, Ecuador, and the United States, referred to here as the “South America/North America-4” lineage.